2022
DOI: 10.3389/fpsyg.2022.854474
|View full text |Cite
|
Sign up to set email alerts
|

Four Weeks of a Neuro-Meditation Program Improves Sleep Quality and Reduces Hypertension in Nursing Staff During the COVID-19 Pandemic: A Parallel Randomized Controlled Trial

Abstract: The purpose of this study was to examine the effectiveness of a neuro-meditation program to support nurses during the COVID-19 pandemic. Forty-five (10 men and 35 women) nurses were classified into three groups based on their systolic blood pressure: normotensive (G-nor; n = 16, 43.8 ± 11.0 year), hypertensive (G-hyp; n = 13, 45.2 ± 10.7 year) and control (G-con; n = 16, 44.9 ± 10.6 year). Using a parallel, randomly controlled design across a 4-week period, 10 × 30-min sessions using the Rebalance© Impulse wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Participants included nurses working night shifts, evening/night shifts, rotating shifts, and dayshifts, yet 15 studies did not specify the work shifts. Although most studies included healthy participants, seven studies included nurses with baseline sleep/fatigue/health complaints (Hausswirth et al, 2022; Huang et al, 2013; Morimoto et al, 2016; Mousavi et al, 2020; Niu et al, 2021; Yazdi et al, 2017; Zhou et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants included nurses working night shifts, evening/night shifts, rotating shifts, and dayshifts, yet 15 studies did not specify the work shifts. Although most studies included healthy participants, seven studies included nurses with baseline sleep/fatigue/health complaints (Hausswirth et al, 2022; Huang et al, 2013; Morimoto et al, 2016; Mousavi et al, 2020; Niu et al, 2021; Yazdi et al, 2017; Zhou et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Hausswirth et al (2022) found that a 4‐week light stimulation and mindfulness training program significantly improved sleep quality, sleep efficiency, and fragmentation index as assessed by actigraphy in the intervention compared to control group. Booker et al (2022) found no significant differences in sleep outcomes between intervention and control groups, but significant improvements in insomnia severity and functional outcomes of sleep quality as assessed by ISI and FOSQ‐10 compared to the baseline among nurses receiving a shift work and sleep education plus coaching sessions with individualized strategies on behavior changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this finding and the potential for continued pressure from the COVID‐19 epidemic, we propose the following recommendations: (i) Given the high prevalence of poor sleep quality in dialysis patients, healthcare workers in dialysis centres should develop appropriate non‐pharmacological therapies to alleviate this phenomenon. Some studies have shown that mindfulness meditation improves sleep quality in the general population and COIVD‐19 patients (Desai et al, 2021 ; Hausswirth et al, 2022 ; Li et al, 2022 ). (ii) Policymakers should focus on the psychological status of the chronically ill population, who, after all, have to deal with both physical and psychological stress caused by COVID‐19 (Bonenkamp et al, 2021 ; Urquhart‐Secord et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the FIRST demonstrates stability across time (Jarrin et al, 2016) and stressor types (Table 1), aggregates in families (Drake et al, 2008), and is substantially heritable (Drake et al, 2011;Fernandez-Mendoza et al, 2014), sleep reactivity appears to be a trait predisposition seemingly unfit as a treatment target. Yet, emerging evidence that sleep reactivity is amenable to behavioural interventions belies its trait-like qualities (Cheng et al, 2022;Hausswirth et al, 2022;Okajima, Akitomi, et al, 2020;Okajima et al, 2021;Park et al, 2022;Yang et al, 2023), with some findings even suggesting reductions in FIRST help mediate recovery from insomnia (Cheng et al, 2022;Ubara et al, 2022). et al, 2022).…”
Section: Can We Become Less Sleep Reactive?mentioning
confidence: 99%